ダイ43ジ ナンキョク チイキ カンソクタイ エットウ ホウコク 2002-2003 - 神山, 孝吉; カミヤマ, コウキチ; Kamiyama, Koukichi (2004)
P(論文) 第43次南極地域観測隊越冬隊(第43次越冬隊)40名は,2002年2月1日から翌年1月31日まで1年間昭和基地での越冬観測に従事した.定常観測に加えて,第VI期5カ年計画の初年次としての観測計画のもとで,プロジェクト研究観測とモニタリング観測などを実施した.昭和基地では,様々なゾンデの集中連続飛揚による成層圏観測などを行った.内陸域では,ドームふじ観測拠点を整備・再開し,第44次ドーム越冬隊に引き継いだ.期間中,昭和基地周辺の海氷状態は安定しており,野外活動も精力的に実施することができた.9月のブリザードは基地建物周辺を大きなドリフトで覆い,その後除雪には多大な労力を有した.しかしながら,ドリフトで覆われた海氷部分は,日射の強い夏期にも比較的安定した状態で維持された.最も大きな事故としては,12月後半に大型雪上車SM100型が昭和基地付近の大陸でクレバスを踏み抜いたことがあげられる. The wintering party of the 43rd Japanese Antarctic Research Expedition (JARE), consisting of 40 personnel, carried out observation programs from February 1st, 2002 to January 31st, 2003. As the first year under the VIth five-year JARE programs, various projects and monitoring observations were conducted, as well as routine observation programs. One of the new observations at Syowa Station was continual launching of various sondes as the first stage to clarify the ozone depression in the stratospheric environment. In the inland plateau, Dome Fuji Camp was reopened for the following winter to conduct the deep ice coring project. Field activities were also carried out under stable sea ice conditions around the Ongul Islands during the wintering season. A blizzard in the middle of September brought much snow over the roofs of the station buildings, resulting in much work to be recoued. However, snow cover caused by the blizzard contributed to the stability of sea ice during the coming summer season. The biggest accident during the winter was that an over snow vehicle, SM100, got stuck in a crevasse on the ice sheet coast near Syowa Station in late December. departmental bulletin paper